School Psychology: A Conceptual Approach and a Diachronic Reading - djaalab, nourdine (El Omda in Linguistics and Discourse Analysis, 2023)
School Psychology is no longer a mere specialized theoretical scientific subject, but has become a daily practice carried out by highly experienced and professional psychologists through which they provide psychological services at the level of educational institutions. School Psychology could reach what it reached as a result of knowledge accumulation that spanned over centuries of theorization. This paper will attempt to address the concept of School Psychology, its origin and development, its most important founders and theorists, and it will shed light on its most important topics and contributions to achieving students’ mental health.